PERTUMBUHAN IKAN NILA NIRWANA (Oreochromis niloticus) PADA SISTEM BIOFLOK DENGAN SUMBER KARBON EKSTERNAL DARI TEPUNG SORGUM MANIS (Sorghum bicolor) - Nurhatijah Nurhatijah; Mulyanti Mulyanti; Endiyani Endiyani; Ahmad Supriatna (Universitas Sriwijaya, 2022)
Biofloc technology (BFT) is an alternative that can be used to provide additional feed source in addition to control and improve water quality for aquaculture. BFT can be done by adding an organic carbon source to increase the C/N ratio in the culture media to stimulate the growth of heterotrophic bacteria. The results of the observation were that the highest specific growth rate was obtained in treatment B (5ml floc) with an average value of 2.80 grams/day. The highest average length value in treatment B (5ml floc) reached 10.26 cm. The highest survival rate was in treatment B (5ml floc) with an average value of 86.78%. The highest efficiency value was found in treatment B (5ml floc) with an average of 95.90%. Based on Duncan's further test (p<0.05) the application of biofloc with an external carbon source from sweet sorghum had a significant effect on the specific growth rate, absolute growth, survival rate and feed efficiency of tilapia fry. Keywords : Biofloc; Sweet Sorghum; Tilapia Nirwana ; Aquacukture